Anesthesia for Cesarean Delivery in the Czech Republic: A 2011 National Survey. Issue 1 (March 2016) - Stourac, P.; Blaha, J.; Klozova, R.; Noskova, P.; Seidlova, D.; Brozova, L.; Jarkovsky, J.
Abstract : ( Anesth Analg. 2015;120:1303–1308) Obstetric anesthesia and analgesia care were not regularly monitored in the Czech Republic before the formation of the Expert Committee of Labor Anesthesia and Analgesia (ESPAA) in 2010. In 2011, the ESPAA launched a national project, "Obstetric Anesthesia and Analgesia Month Attributes in the Czech Republic (OBAAMA-CZ), " in order to improve care. The first goal of the project was observing and documenting current practices and techniques. The purpose of this article is to summarize this project's findings as they relate to cesarean delivery.